Histology, Histochemistry and Ultrastructure of Epidermis in Deer, Goat and Sheep - Maya, S. (Indian Journal of Veterinary Anatomy, 2020)
Histology, histochemistry and ultrastructure of epidermis was studied in deer, goat and sheep. The skin consisted of two layers, viz. a superficial epidermis and the deeper dermis. Sweat and sebaceous glands, as well as hair follicles, were epidermal structures located in the dermis and subcutis. Epidermis was composed of stratified squamous keratinized epithelium. Among all the 27 regions studied in the three species, muzzle region had the thickest epidermis. Among the five layers of the epidermis, stratum basalis, stratum spinosum andstratum corneum were always present and formed continuous layers throughout the body surface. Stratum granulosum consisting of one to three layers of cells was a continuous layer in most of the regions. A definite stratum lucidum was seen only in the muzzle, dorsal nasal and ventral abdominal areas. PAS and Alcian blue positive areas were detected in stratum spinosum and stratum granulosum. The latter exhibited positive reaction as green fluorescence to fluorescein iso-thiocyanate conjugated lectin from Ulex europaeus. Intensity of reaction was more in sheep among the three species studied. Epidermis exhibited diffused positive reaction for oil red o.The epidermis showed a positive alkaline phosphatase reaction exept stratum corneum. A diffused positivereaction to acid phosphatase was noticed in epidermis. Melanocytes and keratin pigments in the different layers of skin exhibited a positive reaction in immunohistochemistry due to antigen-presenting immune cells i e. Langerhans cells. Transmission electron microscopy revealed cells in epidermis with keratohyaline granules.